Analysis of the Relationship among Kidney Volume, Obesity, and Blood Pressure in Mexican-American Children - Wang, Hongwei; Quintana, Fernando G; Cervantes, Francisco J; Faz, Margarita (Journal of Pediatric Nephrology, 2019)
Background and Aim: Obesity causes a decrease kidney function and an increase in kidney volume. The aim of this study was to understand the relationship among kidney volume, obesity and blood pressure in Mexican-American children in South Texas. Methods: To study those effects, data was collected from 454 ultrasound done on 289 girls and 762 ultrasound done on 382 boys visiting a pediatric clinic in South Texas from 2003 to 2018. The relationship between kidney volume and obesity was analyzed. IBM SPSS is used for data analysis. Results: Children with fatty livers have a higher kidney volume when compared to children with non-fatty livers. When comparing children classified as BMI percentile (0, 50%), BMI percentile [50%, 85%), BMI percentile [85%, 95%), and BMI percentile above 95%, the kidney volume is increasing as BMI percentile increases. We also found that there is a positive relationship between the kidney volume and systolic blood pressure. Children with high systolic blood pressure (above 119 mmHg) have a larger volume when compared to children with low blood pressure (above 110 but less than or equal 119 mmHg), 110 and below mmHg. Conclusion: Obesity causes inflammation, and lipid accumulation. These effects can cause an increase in kidney volume. Kidney volume increases can be caused by hypertension. This is even severe for Mexican-American children in south Texas. Keywords: Obesity; Kidney volume; Hypertension; Child.